2021
DOI: 10.1128/aac.00143-21
|View full text |Cite
|
Sign up to set email alerts
|

Lytic Bacteriophages Facilitate Antibiotic Sensitization of Enterococcus faecium

Abstract: Enterococcus faecium, a commensal of the human intestine, has emerged as a hospital-adapted, multi-drug resistant (MDR) pathogen. Bacteriophages (phages), natural predators of bacteria, have regained attention as therapeutics to stem the rise of MDR bacteria. Despite their potential to curtail MDR E. faecium infections, the molecular events governing E. faecium-phage interactions remain largely unknown. Such interactions are important to delineate because phage selective pressure imposed on E. faecium will und… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 73 publications
(96 reference statements)
1
50
0
Order By: Relevance
“…Enterococcal phage phylogeny was determined using OrthoMCL (39) as described previously (24). Enterococcal phage genomes were downloaded from the INPHARED phage genome database (18).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Enterococcal phage phylogeny was determined using OrthoMCL (39) as described previously (24). Enterococcal phage genomes were downloaded from the INPHARED phage genome database (18).…”
Section: Methodsmentioning
confidence: 99%
“…Both phages VPE25 and VFW bind to E. faecalis through cell surface polysaccharides, and infection proceeds following viral DNA entry which requires PIP EF (23). Studies in E. faecium have identified cell wall polysaccharides, secreted antigen A, and RNA polymerase to be involved in phage infection (12, 24). Other studies have identified the enterococcal polysaccharide antigen (Epa) as a co-receptor for E. faecalis phages (25, 26).…”
Section: Introductionmentioning
confidence: 99%
“…The absence/variability of epa genes suggests that the EPA polysaccharides of the 2 species have different sugar compositions, and, in consequence, may confer diverse physiological functions. The epa loci were adapted from [ 10 , 20 , 32 , 54 , 104 , 105 , 107 ]. All genes are drawn to scale.…”
Section: Polysaccharides In the Development Of Complex Multicellular Communitiesmentioning
confidence: 99%
“…Changes in the composition of EPA caused by mutations in the epa loci have also been shown to decrease sensitivity to antibiotics that target cell envelope synthesis, such as ceftriaxone or carbapenems in agar plates with Etest strips [ 54 , 55 ]. This adaptation is thought to result in part from reduced rhamnose and/or increased mannose abundance in some of these strains’ cell wall polysaccharides [ 55 ].…”
Section: Polysaccharides In Enterococcal Adaptation To Harsh Conditionsmentioning
confidence: 99%
See 1 more Smart Citation